PENGARUH KEPUASAN KERJA PADA ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) DENGAN KOMITMEN TIM SEBAGAI VARIABEL PEMODERASI - Cahyono, Edi (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2013)
The purpose this study to examine the effect job satisfaction on Organizational Citizenship Behaviour (OCB), effect team commitment on Organizational Citizenship Behaviour, and moderating effect of team commitment on the effect job satisfaction on OCB. The previous research that are inconsistent and remarkably little research has examined OCB in the context of these team motivate researchers to reexamine the influence of job satisfaction on OCB. The sampel taken are 34 employee PT. PLN (Persero) APJ Surakarta. The sampling technique with the sampling jenuh (sensus). Methods used to test the research hypothesis is multiple linear regression and Moderated Regression Analysis (MRA). The results show that the job satisfaction positively affect on OCB and team commitment does moderate the effect job satisfaction on OCB. The results of this study support the research of Foote and Tang (2008).